Laugh is in the air: An exploratory analysis of laughter during speed dating - Rathcke, Tamara; Fuchs, Susanne (Frontiers in Communication, 2022)
Laughter is a ubiquitous vocal behaviour and plays an important role in social bonding, though little is known if it can also communicate romantic attraction. The present study addresses this question by investigating spontaneous laughter produced during a 5-minute conversation in a heterosexual speed dating experiment. Building on the posits of Accommodation Theory, romantic attraction was hypothesised to coincide with a larger number of shared laughs as a form of convergence in vocal behaviour that reduces the perceived distance between the daters. Moreover, high-attraction dates were expected to converge toward the same laughter type. The results of the experiment demonstrate that a) laughs are particularly frequent in the first minute of the conversation, b) daters who are mutually attracted show a significantly larger degree of temporal overlap in laughs, c) specific laughter types (classified as a nasal “laugh-snort”) prevail in high-attraction dates, though shared laughs are not consistently of the same type. Based on this exploratory analysis (limited to cisgender, heterosexual couples), we conclude that laughter is a frequent phenomenon in speed dating and gives some indication of mutual romantic attraction.